Hubungan Keberadaan Koloni Bakteri Staphylococcus dan Faktor Fisikawi dalam Ruangan Terhadap Kejadian Sick Building Syndrome (SBS) pada Petugas Perpustakaan Universitas Tanjungpura - Rikhsan Kurniatuhadi, Nuriani, Rahmawati, (Jurnal Protobiont, 2017)
Sick Building Syndrome (SBS) is a group of symptoms experienced by building occupants associated with time spent in buildings that have poor air quality. This research aims to determine the correlation between the factor of the presence of bacteria members of the genus Staphylococcus and indoor physical factors including air temperature, air humidity and light intensity and the occurrences of SBS among library staff of Tanjungpura University. This study used explanatory research method with cross sectional approach conducted from February to July 2017. SBS respondents data were collected using a questionnatres and in depth interviews. In total, 19 respondents were included in this study. The result of analysis of analysis show that there was no correlation between presence of colony of Staphylococcus and most aspects of physical work environment except air humidity p value = 0.003(p value â‰¤ 0.05) and accurences of SBS at the Library of Tanjungpura University.